Design of FSS radome using binary particle swarm algorithm combined with pixel-overlap technique. Issue 5 (24th March 2017) - Liu, Ning; Sheng, Xianjun; Zhang, Chunbo; Fan, Jingjing; Guo, Dongming
Abstract: An optimization method for designing frequency selective surface (FSS) radome using binary particle swarm optimization (BPSO) algorithm combined with pixel-overlap technique is proposed, in this paper. The proposed method takes the connectivity condition of adjacent conductors within FSS element into consideration. With the help of pixel-overlap technique, lattice points in FSS element are avoided by overlapping adjacent conductors, which improves the manufacturability of the FSS layers. Also, structure parameters of the FSS radome can be obtained according to the desired frequency selective property using the BPSO algorithm. To verify the validity of the proposed method, a sandwich-structured FSS radome is designed, fabricated, and measured. Good agreements between the simulation and measurement results can be observed, which demonstrate that the proposed method can be applied to design FSS radome.